MOTIVATION AND ENGAGEMENT OF EMPLOYEES IN WAR AND POST-WAR TIMES: A MANAGEMENT ASPECT - Kopchak, Yurii; Beryslavska, Anna; Bernatska, Iryna (Public Management and Policy, 2026)
This article discusses how approaches to motivating employees have changed and how different their involvement in work at Ukrainian enterprises looks today, in the circumstances of a full-scale military conflict and given that the country must now think about post-war recovery. The topic is acutely relevant, because after February 2022, business in Ukraine faced a reality that no one was prepared for: the usual tools for stimulating personnel turned out to be ineffective, and the employees themselves began to think in completely different categories - not about career advancement, but about elementary safety and psychological balance. The wave of internal displacement, the mobilization of able-bodied people, and the departure of specialists abroad have deepened the personnel problem and forced managers to look for ways to retain and support people in extremely difficult times. The work aims to identify which factors currently have the greatest impact on people's motivation and involvement in Ukrainian organizations, and to formulate practical advice for managers on building an effective personnel policy in both current crisis conditions and the post-war perspective. Methodologically, the study is based on a systematic analysis, comparison and generalization of scientific publications, as well as on the processing of empirical data from sociological surveys and reports of international institutions. The results obtained showed that the war radically reshaped people’s priorities: the most important became a sense of security, stable wages and access to psychological help. At the same time, the role of intangible things has noticeably increased - people want to understand that their daily work has meaning not only for the company, but also for the reconstruction of the country as a whole. The article also summarizes the management practices that domestic enterprises use to maintain their teams, and proposes a step-by-step model for the transition from anti-crisis motivation to strategically oriented motivation. It is concluded that the foundation of post-war management should be flexible HR approaches built around the real needs of specific people, and not around abstract procedures.